Implementation of New Patient Orientation Through Welcome Book in the Locally Advanced Breast Cancer (LABC) Patient: A Case Study - Niken Sari Nuraini; Nurfika Asmaningrum; Alfid Tri Afandi; Ni Made Arik Mulyanti (Health and Technology Journal (HTechJ), 2024)
New patients frequently experience fear or anxiety due to the unfamiliarity of the hospital environment, a phenomenon particularly evident among those with LABC. The introduction of welcome book serves as a potential intervention to enhance patient knowledge and alleviate anxiety. This study evaluates the effectiveness of a welcome book in enhancing patient knowledge and reducing anxiety levels. A case study at a hospital involved a 42-year-old patient with LABC. The study examined the patient's orientation using a welcome book that covered various aspects such as orientation of persons, places, facilities, rules, and educational resources. The patient's knowledge was assessed with a knowledge evaluation sheet, and anxiety levels were measured using the Hamilton Anxiety Rating Scale. The welcome book provided comprehensive information to enhance patient understanding and reduce anxiety. The patient’s pretest knowledge score was 20, which increased to 86.67 after using the welcome book, indicating a substantial improvement. Initially, the patient exhibited mild anxiety upon admission, but after four days of utilizing the welcome book, there was a significant reduction in anxiety levels. The implementation of welcome book for a new patient orientation significantly enhanced the knowledge and reduced the anxiety levels of patient with LABC. This study underscores the importance of comprehensive orientation materials, such as welcome books, in improving patient outcome and suggest hospitals to adopt similar strategies to enhance patient education adn reduce anxiety.